2014
DOI: 10.1177/1362361313516548
|View full text |Cite
|
Sign up to set email alerts
|

Vocational support approaches in autism spectrum disorder: A synthesis review of the literature

Abstract: This synthesis-based analysis identifies and reviews studies evaluating vocational resources for adults with autism spectrum disorder. It is based on a larger systematic review of intervention studies in autism spectrum disorder, from which a critical interpretive synthesis was conducted on studies related to vocation and autism spectrum disorder. In total, 10 studies were found that examine employment support for youth and adults with autism spectrum disorder. Two domains of vocational intervention in the lit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
73
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(79 citation statements)
references
References 39 publications
2
73
0
4
Order By: Relevance
“…This is in line with Nicholas et al (2015) highlighting that, on-the-job support or job coaching may be of particular importance for facilitating preparation for finding a job, including how to apply and interview for a position, and also provide needed support in the work environment. Thus, allowing for the large amount of one-on-one time required of the professional for exploring appropriate job opportunities and supporting the individual in the workplace is a crucial aspect of on-the-job support.…”
Section: Support For the Occupational Transition Processsupporting
confidence: 77%
See 1 more Smart Citation
“…This is in line with Nicholas et al (2015) highlighting that, on-the-job support or job coaching may be of particular importance for facilitating preparation for finding a job, including how to apply and interview for a position, and also provide needed support in the work environment. Thus, allowing for the large amount of one-on-one time required of the professional for exploring appropriate job opportunities and supporting the individual in the workplace is a crucial aspect of on-the-job support.…”
Section: Support For the Occupational Transition Processsupporting
confidence: 77%
“…This is an important finding since concerns have been raised about the "lock-in effects" of day centres, whereby those who come to day cen-tres tend to remain there without transitioning to paid employment (The Swedish National Board of Health and Welfare, 2008). The finding is also important as it indicated that individual placements in a regular workplace, which may be comparable to supported employment, comprising a rapid job search, community placement and job coaching (Nicholas et al, 2015), may support a sense of hopefulness and motivation towards finding employment in the regular labour market.…”
Section: Support For the Occupational Transition Processmentioning
confidence: 93%
“…Therefore, a comprehensive model with collaboration of all partners would potentially lead to effectiveness and efficiency in understanding and solving employment-related problems, and thus to supporting overall vocational success (Certo et al 2008;Hillier et al 2007a, b;Nicholas et al 2014;Shattuck and Roux 2014). Project SEARCH is such a model that involves all of the following components and encourages all partners to collaborate instead of co-exist.…”
Section: Multidisciplinary Collaborationmentioning
confidence: 99%
“…Studies of supported employment programs and vocational rehabilitation services are still limited and are often of poor research quality (12). Burgess and Cimera (13) found that approximately one third of participants with ASDs who participated in a vocational rehabilitation service were employed; however, rates varied between 25% and 50% across the United States.…”
Section: Introductionmentioning
confidence: 99%